DISCRIMINATED FUNCTIONAL COMMUNICATION: A PROCEDURAL EXTENSION OF FUNCTIONAL COMMUNICATION TRAINING - Kuhn, David E (The Society for the Experimental Analysis of Behavior, 2010)
A limitation associated with communication-based interventions for problem behavior is the potential for requesting reinforcement at high rates. Multiple-schedule arrangements have been demonstrated to be effective for controlling rates of responding (Hanley, Iwata, & Thompson, 2001). In the current study, we extended previous research by teaching individuals to attend to naturally occurring discriminative stimuli (e.g., caregiver behavior) instead of arbitrary stimuli (e.g., picture cards). Following successful treatment with functional communication and extinction, 2 participants were taught to request attention differentially based on whether the caregiver was engaging in a variety of “busy” (e.g., talking on the phone) or “nonbusy” (e.g., reading a magazine) activities. Following training, each participant engaged in communication primarily when caregivers were engaged in nonbusy activities.